Pengembangan Kebijakan Menekan Emisi Kendaraan Bermotor Di Indonesia - Sitorus, Panal (Warta Penelitian Perhubungan, 2010)
Levels of air pollution caused by motor vehicles in the big cities in Indonesia is quite high, about 60%was alarming and impact on public health. The main problem is why should conduct an effectivetesting of emissions vehicles in Indonesia? Tire aim of study is to provide recommendations haw toreduce emissions levels, the object of studtj is the implementation of emissions testing, characteristicsand facilities. The method used is to compare with the threshold determined btJ the data from variousofficial. sources.Tire success of reducing emissions levels is in the supervision of testing and legal action in its testingsystem.Need to reform its institutions emissions testing, technician certification, the appointment of calibrationinstitution, improving information systems, certification, and socialization to the communihJcontinuously.Keyword: Emissions and public health.